QUALITY ASSURANCE DENGAN METODEQUALITY FUNCTION DEPLOYMENT: KONSEP IMPLEMENTASI PADA INSTITUSI PERGURUAN TINGGI - Arif, Alfi (JURNAL AKUNTANSI UNIVERSITAS JEMBER, 2011)
This article intent to explore the Quality Function Deployment (QFD) methodology in order to construct quality assurance for the educational institutions..QFD is management tool that provides a visual connective process to help teams focus on the needs of the customers throughout the total development cycle of a product or process. It provides the means for translating customer needs into appropriate technical requirements for each stage of a product/process-development life-cycle. It helps to develop more customer-oriented, higher-quality products, both goods and services. Key words: Quality, Functions, Assurance, Deployment